(untitled) (Western Pacific Surveillance and Response, 2015)
Dengue continues to be a priority emerging disease in the Asia-Pacific. Reported dengue surveillance data for 2012 in the Western Pacific, with nearly 350 000 cases, surpassed that of 2011. The sustained dengue levels and complex epidemiology highlight the continued need for information-sharing on a routine and timely basis.